Recent Clinical Manifestation and Prognosis of Fungal Endophthalmitis: A 7-Year Experience at a Tertiary Referral Center in Korea - Kim, Dong Yoon (J Korean Med Sci, 2015)
This study analyzed the recent causes, prognosis, and treatment strategies for fungal endophthalmitis. A retrospective review of patients who were diagnosed with fungal endophthalmitis at our center was conducted. The fungal organisms isolated from each patient and the visual prognosis according to the route of infection and treatment method were analyzed. A total of 40 eyes from 30 patients with fungal endophthalmitis were included in this study. Candida species were the most common causative organisms in 35 of 40 eyes. Endogenous and exogenous endophthalmitis were observed in 33 and 7 eyes, respectively. Pre- and post-treatment best-corrected visual acuity (BCVA) was not significantly different between endogenous endophthalmitis and exogenous endophthalmitis. The 40 eyes were treated using the following modalities: intravitreal antifungal agent injection with intravenous antifungal agent (16 eyes), vitrectomy with intravenous antifungal agent (14 eyes), intravenous antifungal agent alone (9 eyes), and evisceration (1 eye). Post-treatment BCVA only significantly improved after treatment in the vitrectomy group. Candida species were the most common cause of fungal endophthalmitis, irrespective of the route of infection. The visual prognosis of fungal endophthalmitis was generally poor. In conclusion, if the general condition of the patient tolerates a surgical procedure, prompt vitrectomy and intravitreal injection of antifungal agents can improve visual acuity. GRAPHICAL ABSTRACT: [Image: see text]